2018
DOI: 10.1093/milmed/usx018
|View full text |Cite
|
Sign up to set email alerts
|

Automated Pupillometry and Detection of Clinical Transtentorial Brain Herniation: A Case Series

Abstract: The potential of automated pupillometry to guide the management of severely injured neurologic patients is intriguing and warrants further study in the critical care unit and beyond. The utility of a portable device in the combat setting may allow for triage of patients with severe neurologic injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 43 publications
0
22
0
Order By: Relevance
“…However, in the setting of raised intracranial pressure or uncal herniation or any other neurological emergency, pupillary light response is used to monitor the patients. There have been attempts to use pupillography instead of simple clinical observation to detect a light response (172). Indices based on pupillography have been used, but it is not yet clear if pupillography adds information additional to simple observation.…”
Section: The Efferent Pupillary Pathway Author: Helmut Wilhelmmentioning
confidence: 99%
“…However, in the setting of raised intracranial pressure or uncal herniation or any other neurological emergency, pupillary light response is used to monitor the patients. There have been attempts to use pupillography instead of simple clinical observation to detect a light response (172). Indices based on pupillography have been used, but it is not yet clear if pupillography adds information additional to simple observation.…”
Section: The Efferent Pupillary Pathway Author: Helmut Wilhelmmentioning
confidence: 99%
“…The automated pupillometry exam takes approximately 3 seconds to perform and has been studied in children of all ages without any adverse events, although it may be limited by patient cooperation in awake children. 7 Studies in adult patients support a potential role of the NPi assessed by AIP for prognostication after cardiac arrest and subarachnoid hemorrhage, [8][9][10][11][12] detection of significant intracranial events, [13][14][15] and elevated ICP, [16][17][18][19][20] and for detecting nonconvulsive status epilepticus. 21,22 Published literature established normative data PLR reference values in healthy children, but investigations of AIP use in neurocritically ill pediatric patients are limited to a single study on its use for detection of increased ICP.…”
Section: Introductionmentioning
confidence: 91%
“…Previously discussed studies had noted improvement in the PLR after treatment of increased ICP or TTH, but those reports were descriptive, and the response was not systematically evaluated. 40,58,59 Taylor et al described 2 illustrative cases. In the first, the patient had sustained ICP >20 mm Hg and developed an unreactive pupil with CV <0.6 mm/s.…”
Section: Increased Icp and Herniationmentioning
confidence: 99%
“…58 In the study of 12 herniation events in 3 patients, Papangelou et al reported that NPi normalized with osmotic therapy after a median of 43 minutes. 59…”
Section: Applications Of Quantitative Pupillometrymentioning
confidence: 99%